Recurrent Somatic PDGFRB Mutations in Sporadic Infantile/Solitary Adult Myofibromas But Not in Angioleiomyomas and Myopericytomas. (February 2017) - Agaimy, Abbas; Bieg, Matthias; Michal, Michael; Geddert, Helene; Märkl, Bruno; Seitz, Jan; Moskalev, Evgeny A.; Schlesner, Matthias; Metzler, Markus; Hartmann, Arndt; Wiemann, Stefan; Michal, Michal; et al.
Abstract : Infantile myofibroma (MF) is an uncommon benign myofibroblastic tumor of infancy and childhood. Solitary adult MF shares similar features with infantile MF. The lesions occur in 3 clinicopathologic settings: solitary, multicentric, and generalized and can be either sporadic or familial. Traditionally, infantile MF has been included in the spectrum of infantile hemangiopericytoma. The recent World Health Organization classification listed MF, angioleiomyoma, and myopericytoma under the general heading of perivascular tumors in the sense of a morphologic spectrum of perivascular myoid cell neoplasms . Although activating germline PDGFRB mutations have recently been linked to familial infantile MF, the molecular pathogenesis of sporadic infantile and adult solitary MF remained unclear. In this study, we analyzed 25 solitary MFs without evidence of familial disease (9 infantile and 16 adult MFs) to address the question whether somatic PDGFRB mutations might be responsible for the sporadic form of the disease. Given the presumed histogenetic link of MF to myopericytoma and angioleiomyoma, we additionally analyzed a control group of 6 myopericytomas and 9 angioleiomyomas for PDGFRB mutations. We detected PDGFRB mutations in 6/8 (75%) analyzable infantile and in 11/16 (69%) adult MFs but in none of the angioleiomyomas or myopericytomas. In 2 infantile MFs, additional sequencing of the germline confirmed the somatic nature of PDGFRB mutations. To our knowledge, this is the first study reporting apparently somatic recurrent PDGFRB mutations as molecular driver events in the majority of sporadic infantile and adult solitary MFs. Our results suggest molecular distinctness of MF as compared with angioleiomyoma/myopericytoma. Investigation of more cases including those with atypical and worrisome features, as well as other mimickers in the heterogenous morphologic spectrum of MF, is mandatory for validating the potential diagnostic value of PDGFRB mutation testing as a possible surrogate in difficult-to-classify lesions.